Association between the glucose-to-potassium ratio and delirium in critically ill ICU patients: a retrospective study - He Jiang; Jinhong Zhang; Congcong Han; Hongyu Xu; Jiangling Xia (Scientific Reports)
Abstract It is unclear whether the serum glucose-to-potassium ratio (GPR) is related to delirium in critically ill patients. The aim of this study was to investigate the association between GPR and delirium in critically ill patients in the intensive care unit (ICU). Patients were enrolled from the Medical Information Mart for Intensive Care IV (MIMIC-IV). We extracted the mean values of blood glucose and blood potassium on the first day of admission to the ICU and calculated the glucose-to-potassium ratio using Navicat Premium (16.0). In this study, known risk factors for delirium, including age, sex, duration of mechanical ventilation, benzodiazepine use, opioid use, the Charlson Comorbidity Index (CCI), and the Simplified Acute Physiology Score II (SAPS II), were systematically adjusted through a multivariable logistic regression model. Subgroup analysis was used to determine the risk factors for delirium in critically ill patients. Of the 15,007 patients, 56.2% were males, the median age was 65 years, and the overall incidence of delirium was 16.8% (2528/15007). Multivariate logistic regression analysis revealed that an increased GPR was significantly associated with increased delirium occurrence. The Model 3 adjusted odds ratio for the GPR as a continuous variable was 1.17 (95% CI 1.09–1.26). Model 1 was adjusted for age and sex; Model 2 was adjusted for comorbidities; and Model 3 included clinical, laboratory, and treatment variables. Additionally, the incidence of delirium increased significantly with an increasing GPR (trend test: 1.1 (1.05–1.15); p < 0.01). GPR is an independent predictor of delirium in critically ill ICU patients.